Deficiency of TRIM32 Impairs Motor Function and Purkinje Cells in Mid-Aged Mice - Zhu, Jian-Wei; Jia, Wei-Qiang; Zhou, Hui; Li, Yi-Fei; Zou, Ming-Ming; Wang, Zhao-Tao; Wu, Bing-Shan; Xu, Ru-Xiang (Frontiers in Aging Neuroscience, 2021)
Proper functioning of the cerebellum is crucial to motor balance and coordination in adult mammals. Purkinje cells (PCs), the sole output neurons of the cerebellar cortex, play essential roles in cerebellar motor function. Tripartite motif-containing protein 32 (TRIM32) is an E3 ubiquitin ligase that is involved in balance activities of neurogenesis in the subventricular zone of the mammalian brain and in the development of many nervous system diseases, such as Alzheimer's disease, autism spectrum disorder, attention deficit hyperactivity disorder. However, the role of TRIM32 in cerebellar motor function has never been examined. In this study we found that motor balance and coordination of mid-aged TRIM32 deficient mice were poorer than those of wild-type littermates. Immunohistochemical staining was performed to assess cerebella morphology and TRIM32 expression in PCs. Golgi staining showed that the extent of dendritic arborization and dendritic spine density of PCs were decreased in the absence of TRIM32. The loss of TRIM32 was also associated with a decrease in the number of synapses between parallel fibers and PCs, and in synapses between climbing fibers and PCs. In addition, deficiency of TRIM32 decreased Type I inositol 1,4,5-trisphosphate 5-phosphatase (INPP5A) levels in cerebellum. Overall, this study is the first to elucidate a role of TRIM32 in cerebellar motor function and a possible mechanism, thereby highlighting the importance of TRIM32 in the cerebellum.